How learning about climate change affects intention and willingness to teach: a pre–post study with physics pre-service teachers - Schubatzky, Thomas; Wildbichler, Sarah; Wackermann, Rainer; DeCock, Mieke; Ivanjek, Lana; Micoloi, Magdalena; Pospiech, Gesche (Frontiers in Education, 2025)
Climate change education can act as a social tipping element that accelerates transformative change towards stabilizing Earth’s climate by 2050. As the global climate crisis intensifies, it is increasingly important for teachers to incorporate climate change topics into their teaching. This pre-post study investigates how N = 71 physics pre-service teachers’ (PST) conceptual understanding of climate change is related to their intention and willingness to teach the topic. We applied an extended Theory of Planned Behavior (TPB) model and conducted multigroup path analysis to examine how attitudes, subjective norms, and perceived behavioral control predict physics PSTs’ teaching intentions. The study utilized a pre-post approach, analyzing changes after an intervention designed to enhance climate change understanding. Findings indicate that conceptual understanding significantly predicts self-efficacy and attitudes. Post-intervention, the relationships within the TPB model mainly remained consistent, with an amplified effect of conceptual understanding on self-efficacy and attitudes and an additional direct effect on the physics PSTs’ willingness to teach about climate change. The results underscore the importance of targeted educational interventions in improving teachers’ confidence and attitudes toward teaching climate change by fostering their understanding of climate change. These findings highlight the need for comprehensive teacher education programs to effectively prepare educators for climate change instruction.